The experience of compulsory volunteering: the obstacles for voluntary sector in Post-Soviet countries - Pranaitytė, Irma (Socialiniai tyrimai, 2022)
The aim of this study was to examine the compulsory volunteering experience under the Soviet regime and highlight specific reasons, which keep individuals away from getting involved in activities in voluntary organizations. The paper examines the factors, which keep individuals away from joining voluntary organizations, and examines what influence the experience of compulsory volunteering has. A qualitative research approach has been chosen. Respondents were individuals born between 1945 and 1965 and lived under the Soviet regime. 30 interviews were conducted with individuals who have not been involved in voluntary organizations. The results reveal the understanding of the concept of volunteering, the factors, which keep individuals away from volunteering, and what role the experience of compulsory volunteering has played. Voluntary organizations can use the results in order to encourage potential volunteers to join their voluntary organizations.